Hubungan Andropause dengan Penyakit Jantung Koroner di RSUD Dr. Moewardi Surakarta - Hanne Dianta Pramono; Endang Syahrir; Sigit Setyawan (Nexus Kedokteran Klinik, 2014)
Background : Andropause is a syndrome of aging that can be interpreted by the cessation of physiological processes in men. It is estimated there are at least 25 million men in America between 40 and 55 years have some degree of andropause. The loss of testosterone can occur in men age 35 years , gradually , with testosterone levels decreased only 1 % to 1.5 % per year. Coronary heart disease is a pathological condition of the coronary arteries ( atherosclerosis ) that causes changes in the structure and function of arteries and decrease blood flow to the heart. Coronary heart disease is a major health problem in developed countries . While the cause of death remains ranked No. 3. Study aimed to analyze the correlation between andropause with coronary heart disease in Dr . Moewardi hospitals Surakarta. Methods : This study was an observational analytic cross sectional approach . Subjects were patients with coronary heart disease and who do not suffer from coronary heart disease who present in Cardiac clinic Dr . Moewardi hospital Surakarta . A total of 104 subjects were selected using purposive sampling method . Data were collected by direct interviews and questionnaires . Data were analyzed by multiple logistic regression analysis and processed with the Statistical Product and Service Solutions ( SPSS ) 16.0 for Windows . Results : Patients with coronary heart disease have a risk of andropause with moderate levels of correlation of 0.32 with the use of contingency correlation test. Conclusions : There is a significant association between andropause with coronary heart disease in elderly men in Surakarta Moewardi Hospital with moderate levels of correlation. Keywords : Andropause , Coronary Heart Disease